Virtual occlusal record: a literature review about the digital method (Research, Society and Development, 2021)
To produce prostheses through the digital flow, it is essential to transfer the correct patient’s interocclusal relationship to the digital software program, enabling the articulation of virtual models. Therefore, the aim of this study was to carry out a narrative literature review to describe and discuss aspects related to the virtual occlusal record realization, as well as its precision and accuracy in different clinical situations. Searches for scientific publications were performed in different databases and only articles in English related to the topic were selected. Different methods for the alignment of virtual models are described in the literature, the main one being the scanning of the patient in occlusion, usually in a position of maximum intercuspation. However, this technique may demonstrate disagreement with the patient's actual occlusal relationship due to several factors, and therefore studies were carried out to verify the precision and accuracy of these records. Most studies use plaster models and industrial scanner to capture the record, with few studies performed with intraoral scanner in patients. Despite the various scanner systems available and the different ways of evaluating them, in general, the studies show an adequate precision and accuracy of virtual occlusal records of dentate models. However, the absence of dental elements is related to the lower accuracy of these records, it being necessary to establish an appropriate method of scanning for these clinical situations.